2020
DOI: 10.1038/s41421-020-0167-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation and regulation: toward a better understanding of complex mechanisms

Abstract: Inflammasomes are cytoplasmic multiprotein complexes comprising a sensor protein, inflammatory caspases, and in some but not all cases an adapter protein connecting the two. They can be activated by a repertoire of endogenous and exogenous stimuli, leading to enzymatic activation of canonical caspase-1, noncanonical caspase-11 (or the equivalent caspase-4 and caspase-5 in humans) or caspase-8, resulting in secretion of IL-1β and IL-18, as well as apoptotic and pyroptotic cell death. Appropriate inflammasome ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
492
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(504 citation statements)
references
References 291 publications
(344 reference statements)
1
492
0
11
Order By: Relevance
“…These data are consistent with the observation that NOD2 and RIG-I receptor stimulation induces autophagy, boosts antibacterial effect and antigen presentation, although not in the context of tuberculosis (74,75). Notably, autophagy is linked with inflammasome activation which requires caspase-1, and excessive activation of inflammasome triggers its degradation via autophagy (45,46). Finally, capsase-1 enhances the acidification of phagosomal lumen through the activation of NOX2-phagocyte oxidase (75).…”
Section: Discussionsupporting
confidence: 88%
“…These data are consistent with the observation that NOD2 and RIG-I receptor stimulation induces autophagy, boosts antibacterial effect and antigen presentation, although not in the context of tuberculosis (74,75). Notably, autophagy is linked with inflammasome activation which requires caspase-1, and excessive activation of inflammasome triggers its degradation via autophagy (45,46). Finally, capsase-1 enhances the acidification of phagosomal lumen through the activation of NOX2-phagocyte oxidase (75).…”
Section: Discussionsupporting
confidence: 88%
“…In response to nerve injury, NLRP3 was not only upregulated, but also translocated to the cytoplasm of motoneurons. Increased production of active IL-1β and IL-18 on the side of the injury suggests activation of inflammasomes, since cleavage of these cytokines is one of the best readout parameters of inflammasome activity (Broz and Dixit 2016;He et al, 2016;Zheng et al, 2020). Although the classical site of assembly of inflammasomes is the cytoplasm, a recent study revealed that six out of the 20 examined NLRs were detected in the nucleus as well.…”
Section: Discussionmentioning
confidence: 99%
“…The second version demonstrated that caspase-1 recruitment and the NLRP3 inflammasome assembly reply may be suppressed at high extracellular potassium concentrations in Thp-1 macrophages. It may propose that potassium efflux may also activate NLRP3 [27].…”
Section: Significance For Atherosclerosismentioning
confidence: 99%